2011
DOI: 10.1002/maco.200905579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the molecular structure of some quinones on their corrosion inhibiting action

Abstract: The molecular characteristics obtained by quantum chemical self-consistent field (SCF) calculations of a series of quinones are correlated with the experimentally determined inhibitor efficiency for mild steel corrosion in neutral aqueous medium. It was established that the decrease of the ionization potential and the increase of the dipole moment of the quinone molecules favor the higher protective effect. The electron density and the geometric molecular structure have also been computed and are discussed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Organic compounds are often used as inhibitors [1][2][3] in acidic media, but their wide application requires designing additional substances with effective protective properties. This process is based on the correlation between the molecular structure of the organic compounds and their inhibiting properties [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The substances of the quaternary ammonium salts group [18][19][20][21] show good inhibitive properties in acidic media.…”
Section: Introductionmentioning
confidence: 99%
“…Organic compounds are often used as inhibitors [1][2][3] in acidic media, but their wide application requires designing additional substances with effective protective properties. This process is based on the correlation between the molecular structure of the organic compounds and their inhibiting properties [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The substances of the quaternary ammonium salts group [18][19][20][21] show good inhibitive properties in acidic media.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of how heterocyclic organic compounds form the adsorption film on the metal surface yet is not resolved. [7][8][9] Since 1947, benzotriazole (BTAH) had been considered as an efficient corrosion inhibitor for copper and its alloys. [10][11][12][13] For the low cast, its hydroxy derivative, 1-hydroxybenzotriazole (BTAOH) also has been discussed as corrosion inhibitor for copper, 8,[14][15][16] although it shows a lower inhibition efficient (IE) than BTAH.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested the use of quinones of low reduction potential as corrosion inhibitors. 18 Other studies with similar quinones, in contrast, have shown that the addition of quinones can increase the corrosion of aluminum in aqueous acidic solutions 19 and the corrosion of steel in black liquor. 20 More recently, Schindelholz et al observed that C-22 corroded at surprisingly high rates (circa 20 mm y −1 ) at room temperature in a pharmaceutical liquor containing 2,3-dichloro-5,6dicyano-1,4-benzoquinone (DDQ) and HCl in acetonitrile.…”
mentioning
confidence: 97%